2023
DOI: 10.3892/br.2023.1626
|View full text |Cite
|
Sign up to set email alerts
|

Gut and reproductive tract microbiota: Insights into the pathogenesis of endometriosis (Review)

Abstract: Endometriosis is characterized by the presence of endometrial-like tissue outside the uterus and is associated with an inflammatory immune response. The gut and reproductive tract microbiota constitute a protective barrier against infection by pathogens and regulate inflammatory and immune functions. This review summarizes microbiota imbalance (i.e., dysbiosis) in endometriosis and discusses how dysbiosis influences disease development. The literature was searched for studies published from inception to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The only previous study focused on gut microbiota and adenomyosis was performed in mice and did not find differences regarding alpha and beta diversity between groups. Nonetheless, loss of microbiota diversity is of note the most constant finding of intestinal dysbiosis and has previously been linked to different chronic conditions 33 including endometriosis 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only previous study focused on gut microbiota and adenomyosis was performed in mice and did not find differences regarding alpha and beta diversity between groups. Nonetheless, loss of microbiota diversity is of note the most constant finding of intestinal dysbiosis and has previously been linked to different chronic conditions 33 including endometriosis 34 …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, loss of microbiota diversity is of note the most constant finding of intestinal dysbiosis and has previously been linked to different chronic conditions 33 including endometriosis. 34 …”
Section: Discussionmentioning
confidence: 99%
“…The microbiota, particularly the gut microbiota, has been recognized as a potentially influential factor in various gynecological conditions, including endometriosis 131 . Studies have shown that there may be alterations in the gut microbiota composition in women with endometriosis 131,132 . These changes include differences in the abundance and diversity of certain bacterial species compared with women without the condition.…”
Section: The Microbiota and Postmenopausal Endometriosismentioning
confidence: 99%
“…It is noteworthy that in animal models, transplantation of diseased gut microbiota can induce endometriosis. [ 14 ] Moreover, the transplanted gut microbiota can further promote the growth and expression of inflammation in endometrial lesions. [ 15 ] In contrast, models of endometriosis developed in mice and rhesus monkeys also manifest changes or dysbiosis in gut microbiota.…”
Section: Introductionmentioning
confidence: 99%